Manajemen Konflik Interpersonal Ingroup Kaum Homoseksual Dalam Interaksi SosialDi Kota Makassar - Sabar, Hary; Bahfiarti, Tuti (KAREBA : Jurnal Ilmu Komunikasi, 2020)
This study focuses and aims to describe the interpersonal conflict management of homosexuals in interacting in the city of Makassar in ingroup and outgroup. Using a qualitative approach, data were taken from the field as a result of in-depth interviews with homosexual informants, two gays and two lesbians in the city of Makassar. The results of this study indicate that each informant has a different way of resolving conflicts depending on the form and type of conflict affecting the way conflict resolution of homosexuals. Efforts to deal with lesbian conflict are easier to deal with in-group conflicts than in outgroup conflicts. Conversely, gays are easier to deal with outgroup conflicts than ingroup conflicts.